Soybean production under drought stress with application of Bradyrhizobium japonicum induced by genistein - Yaya Hasanah; Nini Rahmawat (Syiah Kuala University, 2012)
A research about production of soybean under drought stress with the application of Bradyrhizobium japonicum induced by genistein was conducted in green house, Faculty of Agriculture, University of Sumatera Utara. The aim of the research was to study the role of B. japonicum induced by genistein on soybean production. The experiment used Randomized Complete Block Design Factorial with three factors. The first factor was genistein treatments consisted of without and with genistein. The second factor was B. japonicum consisted of without B. japonicum, B. japonicum isolate 1, B. japonicum isolate 2 and B. japonicum isolate 3. The third factor was soil water content condition namely 40%, 60% and 80% of field capacity. The parameters observed were plant growth rate, relative growth rate, nett assimilation rate, dry weight/plant and dry weight of 100 seeds. The result research showed that the treatment of interaction between B. japonicum induced genistein under 80% of field capacity gave the higher plant growth rate, plant growth rate, relative growth rate, nett assimilation rate and dry weight of 100 seeds.